Factors Influencing College Students’ Use Behavior of Online Learning Platforms in Sichuan, China - Zhu, Lihua (Scholar: Human Sciences, 2025)
Purpose: After the COVID-19 pandemic, online learning has become an essential approach for undergraduates to pursue study in higher education institutions. This study investigates the factors that affected the college students’ use behavior when applying to online learning platforms in Sichuan, China, including perceived ease of use, usefulness, attitude, social influence, facilitating conditions, behavioral intention, and use behavior. Research design, data, and methodology: 500 undergraduates in a college were taken as the research respondents. The validity and reliability of the variables were confirmed through the IOC (Item-Objective Congruence) and Pilot test (n=43) prior to collecting data. Construct validity (convergent and discriminant validities) and goodness of model fit were confirmed through the test of Confirmatory Factor Analysis (CFA), and relationships among variables were validated through the Structural Equation Model (SEM). Results: Perceived ease of use strongly affects perceived usefulness. Both perceived ease of use and perceived usefulness are strong predictors of attitude. Behavioral intention is influenced by attitude, perceived usefulness, and social influence. Positive behavioral intention leads to use behavior. However, facilitating conditions have no significant impact on behavioral intention. Conclusion: The research results provide teachers and administrations of the higher education system with a perspective to optimize their teaching methods and policies to promote college students’ utilization of online learning platforms.